Developing E-Module Material on the Digestive System in Animals to Improve Students' Critical Thinking Ability and Independence - Faridah, Indah; Saptono, Sigit; Isnaeni, Wiwi (Journal of Innovative Science Education, 2023)
The potential that must be developed and formed in tertiary institutions is the ability to think critically and be independent. In addition, equalization of learning outcomes through education at the KKNI level (Indonesian National Qualifications Framework) which states that students graduating from diploma 4 or undergraduate programs are equivalent to level six, where graduates are expected to have logical, critical thinking and are expected to be able to demonstrate independent, quality, and measurable performance. This study aims to analyze the validity of the e-module, test the effectiveness of the e-module in increasing critical thinking skills and independence in learning animal physiology from the digestive system material, and examine student responses related to the e-module. This study uses the 4-D Thiagarajan model (Define, Design, Develop and Disseminate). Based on the results of the recapitulation of the e-module assessment by the material and media expert validator, it was stated that the e-module on the digestive systems of animals is very suitable for use in learning. The effectiveness of the digestive system e-module in animals related to the ability to think critically and independently before and after using the digestive system e-module experienced an increase in critical thinking skills and independence in the moderate category. The results of the observation data on student independence in learning are very good. Student responses to the use of e-modules as learning media can make it easier for students to understand learning material, especially material about the digestive system.